Occurrence, spatial distribution, and key determinants of typical herbicide residues in agricultural soils of northeast China - Meiqi Jiang; Ruiting Dong; Dan Yang; Lixia Zhao; Yang Sun (Environmental Pollution, 2026)

Seed-associated Pseudomonas enhance the growth of Ambrosia trifida - Xue Chen; Chunying Li; Chang Wang; Jieyu Yang; Ruiting Ju; Fengjuan Zhang; Jihua Wu (Plant and Soil, 2026)

From suppression to selection: Chlorination drives biofilm adaptation and resistance in raw water distribution systems - Xiuwen Li; Ruiting Li; Kaiqing Bian; Qing Zhou; Yang Pan; Peng Shi; Aimin Li (Water Research, 2026)

Efficient degradation vs. enhanced persistence: How soil nutrients drive divergent pesticide fates via microbial strategies on the Tibetan plateau - Ruiting Dong; Meiqi Jiang; Dan Yang; Jie Li; Ruigang Wang; Liping Weng; Yang Sun (Environmental Research, 2026)

Pan-cancer characterization of the pyrimidine catabolic enzyme UPB1 identifies a tumor-suppressive prognostic biomarker in skin cutaneous melanoma - Yingli Men; Yi Shao; Yongfeng Chen; Ping Wang; Yiyang Li; Zhenzhen Yang; Ruiting Feng; Hui Wang; Yinsen Song; Cong Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A T-DINEOF model for multiple oceanic variables reconstruction - Bo Ping; Ruiting Yang; Yunshan Meng; Fenzhen Su; Cunjin Xue (Ocean Science, 2026)
Satellite-derived oceanic data are frequently affected by cloud cover, resulting in spatiotemporal gaps. The Multi-DINEOF method is widely used to reconstruct multiple oceanic variables. However, Multi-DINEOF essentially remains a matrix-based DINEOF approach and does not fully leverage the correlations among multiple variables. To address this limitation, this study proposes the T-DINEOF model, aiming to improve the accuracy of reconstructing multiple oceanic variables simultaneously. When applied to sea surface temperature (SST), sea surface chlorophyll a (SCHL), and sea surface wind (SSW) collectively, T-DINEOF reduces root mean square error (RMSE) by 12.9 %, mean absolute error (MAE) by 13.8 %, and mean absolute percentage error (MAPE) by 11.9 % compared to Multi-DINEOF. For each individual oceanic variable, T-DINEOF outperforms both Multi-DINEOF and the original DINEOF methods, reducing RMSE by 9.0 % and 14.7 %, MAE by 10.5 % and 14.6 %, and MAPE by 13.7 % and 13.4 % for SST; reducing RMSE by 9.3 % and 11.8 %, MAE by 9.9 % and 13.4 %, and MAPE by 8.3 % and 11.8 % for SCHL; and reducing RMSE by 16.6 % and 3.7 %, MAE by 16.8 % and 3.5 %, and MAPE by 16.4 % and 3.1 % for SSW. Additionally, T-DINEOF proves effective in regions with a high proportion of missing data and in cases of low data correlation.

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Corrigendum to “Development of active sustainable films based on phytic acid and silicate/polyvinyl alcohol hybrid system for wrapping chicken meat” [Food Packaging and Shelf Life 54 (2026) 101720] - Chaoqun Li; Fanyu Meng; Yongyan Yang; Jingfei Wang; Ruiting Zhang; Chongruihan Li; Yue Wang; Jia Wang; Yan Gao; Shuangling Zhong; Xuejun Cui (Food Packaging and Shelf Life, 2026)

SIRT6 inhibits intermittent hypoxia-induced lung injury by stabilizing NRF2 - Ruiting Qin; Zhijuan Liu; Ran Li; Yongxia Li; Yuan Yang; Li Ai (Tissue and Cell, 2026)

Evolution and consistency analysis of plastic pollution control policies in East Asian Seas countries - Yang Deng; Danning Lu; Mahesh Pradhan; Panate Manomaiviboold; Kittiphon Boonma; Ruiting Wu; Toan Van Pham; Pattayaporn Unroj; Souvanna Phengsisombounf; Chuanbin Zhou (Marine Pollution Bulletin, 2026)

The role of easily biodegradable organic materials as soil biostimulants in mediating the rapid enhancement of soil aggregate stability - Zheng MA; Xinlei ZHANG; Yujian WANG; Luyao YANG; Ruiting GUO; Longtao TU; Zhenlun LI (Pedosphere, 2026)

Development of active sustainable films based on phytic acid and silicate/polyvinyl alcohol hybrid system for wrapping chicken meat - Chaoqun Li; Fanyu Meng; Yongyan Yang; Jingfei Wang; Ruiting Zhang; Chongruihan Li; Yue Wang; Jia Wang; Yan Gao; Shuangling Zhong; Xuejun Cui (Food Packaging and Shelf Life, 2026)

Biodegradable cellulose-based electrostatically assisted air filter with high filtration efficiency and low resistance for sub-micron PMs - Jingyi Nie; Yueqing Li; Tingting Jiao; Ruiting Yang; Meiyun Zhang (Chemical Engineering Journal, 2026)

Biodegradable microplastics exert differential impacts from polyethylene on pesticide fate in soil-earthworm systems: insights into degradation selectivity and microbial mechanisms - Dan Yang; Ruiting Dong; Furong Fu; Lixia Zhao; Xiaojing Li; Huike Ye; Mohan Bai; Yang Sun (Environmental Pollution, 2026)

Conditional Generative Adversarial Networks Enhance Atmospheric Thermodynamic Profile Retrieval from Ground-Based Microwave Radiometer Measurements - Disong Fu; Xia Li; Jingmiao Zhu; Dazhi Yang; Ruiting Liu; Hongrong Shi; Guangyu Gao; Xinlei Han; Xiang’ao Xia; Yunjie Xia; Maoling Ayitikan; Kai Cheng; et al. (Journal of Meteorological Research, 2025)

Carbon black induced pulmonary fibrosis through piR-713551/PIWIL4 targeting THBS2 signal pathway - Mengruo Wang; Yong Niu; Qingping Liu; Peihao Yang; Mengqi Wu; Ruiting Wu; Beibei Shi; Jiawei Chen; Jingyuan Wang; Zhe Du; Yaxian Pang; Lei Bao; et al. (Journal of Environmental Sciences, 2025)

Integrating photo-Fenton-like Fe3O4/CdS-O modules into sponge-based gel solar evaporator for synergistic water regeneration and pollutant degradation - Xuyao Qiao; Shuguang Ning; Hongyao Zhao; Ruiting Ni; Wanyu Zhang; Yangping Zhang; Linzhi Zhai; Danhong Shang; Yanyun Wang; Tongyi Yang; Mengnan Wang; Fu Yang (Journal of Environmental Chemical Engineering, 2025)

Polystyrene bead ingestion promotes atherosclerosis plaque progression via BMP signaling in mice - Na Yang; Bo Wu; Xiaoxue He; Junhu Ma; Longhao Dai; RuiTing Ma; Tingting Yang; Xiaoxi Ning; Xiaoyan Li; Shaobin Jia (Food and Chemical Toxicology, 2025)

Enabling kinetics matching in electrocatalytic ammonia synthesis by leveraging spatially-confined Cu/Fe2O3 heterointerfaces to maximize *H supply and utilization - Mengting Liu; Fu Yang; Hongyao Zhao; Xiu Zhong; Ruiting Ni; Kwame Nana Opoku; Zhenxiao Wang; Yangping Zhang; Yanyun Wang; Feng Zeng; Yinlong Zhu; Weidong Shi (Chemical Engineering Journal, 2025)

Biodegradable air filter with electrospun composite nanofibers and cellulose fibers dual network: Enhanced electrostatic adsorption, humidity resistance, and extended service life - Jingyi Nie; Binrong Sun; Tingting Jiao; Jianfei Liao; Meiyun Zhang; Ruiting Yang; Yueqing Li (Journal of Hazardous Materials, 2025)

Oligo-residual disease in metastatic ALK-positive NSCLC treated with alectinib - Xi Yang; Xiao Chu; Ruiting Ye; Jianjiao Ni; Ya Zeng; Yue Zhou; Qing Xia; Shengping Wang; Qiao Li; Shuai Liu; Zhengfei Zhu; Li Chu (Clinical & Experimental Metastasis, 2025)

Foxp3 inhibits PCV2 replication by reducing the ATPase activity of Rep - Ruijiao Jiang; Qiuyan Huang; Ruiting Shen; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2025)

Biofilm formation dynamics in long-distance water conveyance pipelines: Impacts of nutrient levels and metal stress - Yifan Hu; Ruiting Li; Kaiqin Bian; Qing Zhou; Yang Pan; Lin Ye; Aimin Li; Peng Shi (Water Research, 2025)

Electron-deficient asymmetric Co centers marry oxygen vacancy for NO3RR: Excellent activity and anion resistance property - Hao Lu; Kwame Nana Opoku; Zhenxiao Wang; Ruiting Ni; Mengting Liu; Yanyun Wang; Yangping Zhang; Chao Yu; Aihua Yuan; Fu Yang; Weidong Shi (Chemical Engineering Journal, 2025)

Cropland Exposure to Extreme Dryness and Wetness in China Under Shared Socioeconomic Pathways - Ruiting Yang; Guojie Wang; Yunxia Zhang; Peng Zhang; Shijie Li; Pedro Cabral (International Journal of Climatology, 2025)
Global warming by human activities have exacerbated the occurrence of extreme climatic events, which have taken a huge toll on human production and livelihoods. Predicting future changes in extreme wetness and dryness, along with the extent of cropland exposure to these conditions under various scenarios, is essential for effective climate adaptation and achieving sustainable development goals. This study employs the Standardised Antecedent Precipitation Evapotranspiration Index (SAPEI) method to identify extreme dryness and extreme wetness in China for future projections (2021–2100), and to analyse the characteristics of changes in the pixel‐day, intensity, and affected area by extreme dryness and wetness, as well as the cropland exposures to them under different shared socioeconomic pathways (SSPs). We find that the intensity and spatial extent of extreme dryness and wetness significantly increase in future climate projections, especially under high‐emission scenario compared to low‐emission scenario. Under the scenarios with increased emissions, the cropland exposure increased in most parts of China. Therefore, it is particularly urgent to keep the low‐emission scenario in order to minimise the cropland damage caused by extreme drought and wetness in China in the future.

Polymer tethering strategy modified ZIF67 derived cobalt-confined nanocage for norfloxacin degradation: Tailored reactive sites and beneficial local microenvironment - Hongyao Zhao; Enxian Yuan; Kwame Nana Opoku; Mengting Liu; Xiu Zhong; Ruiting Ni; Zhenxiao Wang; Yanyun Wang; Zengjing Guo; Chongchen Wang; Fu Yang (Chemical Engineering Journal, 2024)

A multi-layer antimicrobial cellulose filter with electrostatic adsorption properties prepared by coating cellulose with chitosan and CuO - Jingyi Nie; Jianfei Liao; Tintin Jiao; Binron Sun; Meiyun Zhang; Ruiting Yang; Yueqing Li (Chemical Engineering Journal, 2024)

Layered deposited MoS2 nanosheets on acorn leaf like CdS as an efficient anti-photocorrosion photocatalyst for hydrogen production - Yao Wang; Tengyang Gao; Ruiting Li; Yan Chen; Wen Luo; Yang Wu; Yu Xie; Yong Wang; Yifan Zhang (Fuel, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Corrigendum to “Horizontal transfer of antibiotic resistance genes within the bacterial communities in aquacultural environment” [Sci. Total Environ. 820 (2022) 153286] - Songzhe Fu; Qingyao Wang; Rui Wang; Yixiang Zhang; Ruiting Lan; Fenglan He; Qian Yang (Science of The Total Environment, 2024)

Unraveling the generation mechanism of singlet oxygen in Bi2WxMo1-xO6 solid solution and roles in photocatalytic degradation of gaseous toluene under visible-light irradiation - Shaobo Cao; Lei Wu; Jun Li; Yang Li; Kang Da; Wenting Chen; Ruiting Xue; Jian Yang; Ximei Fan (Journal of Environmental Chemical Engineering, 2024)

Investigating synergism and mechanism during sequential inactivation of Staphylococcus aureus with ultrasound followed by UV/peracetic acid - Yun Bai; Yuanhang Zhou; Ruiting Chang; Yingying Zhou; Xueli Hu; Jiawei Hu; Chuanyao Yang; Jiabo Chen; Zhi Zhang; Juanjuan Yao (Journal of Hazardous Materials, 2024)

The role of total antioxidant capacity and malondialdehyde of seminal plasma in the association between air pollution and sperm quality - Lipeng Li; Tengfei Feng; Ruiting Wu; Yaling Zhang; Ning Wang; Mengqi Wu; Yaxian Pang; Sujuan Yang; Aimin Yang; Dengsuo Zhang; Guimin Hao; Rong Zhang (Environmental Pollution, 2023)

Chitosan-based mussel-inspired hydrogel for rapid self-healing and high adhesion of tissue adhesion and wound dressings - Yongyan Yang; Ying Ma; Jingfei Wang; Liru You; Ruiting Zhang; Qingye Meng; Shuangling Zhong; Wenqi He; Xuejun Cui (Carbohydrate Polymers, 2023)

Enhanced inactivation of Escherichia coli by ultrasound combined with peracetic acid during water disinfection - Yun Bai; Chunhai Shi; Yuanhang Zhou; Yingying Zhou; Haocheng Zhang; Ruiting Chang; Xueli Hu; Jiawei Hu; Chuanyao Yang; Kedi Peng; Ping Xiang; Zhi Zhang (Chemosphere, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Effects of seasonal ambient heat stress on expression of microRNAs in the mammary gland of Holstein cows - Caiyun Fan; Ruiting Hu; Haixiao Fan; Ying Yang; Bin Gong; Shaoze Zhang; Jianping Ding; Yanjing Su; Zhao Zhuo; Jianbo Cheng (International Journal of Biometeorology, 2021)

Semi-synthetic product dihydroartemisinin inhibited fibronectin-1 and integrin-β1 and interfered with the migration of HCCLM6 cells via PI3K-AKT pathway - Ruiting Wu; Yan Gao; Jiaqin Wu; Chunli Wang; Li Yang (Biotechnology Letters, 2020)

An experiment to improve the capability of the regional climate model RegCM4.5 to simulate the land surface climate in dense vegetation areas - Minghao Yang; Ruiting Zuo; Liqiong Wang; Fengliang Hu; Chao Wang; Wei Ge (Journal of Earth System Science, 2019)

Characterization of the complete chloroplast genome sequence of Cardamine macrophylla (Brassicaceae) - Ting Ren; Yanci Yang; Jiao Wang; Ruiting Zhang; Zhan-Lin Liu (Conservation Genetics Resources, 2018)